Ablation of the right cardiac vagus nerve reduces acetylcholine content without changing the inflammatory response during endotoxemia - Plaschke, Konstanze; Uhle, Florian; Brenner, Thorsten; Weigand, Markus A.; Kopitz, Jürgen (International journal of molecular sciences, 2018)
Acetylcholine is the main transmitter of the parasympathetic vagus nerve. According to the cholinergic anti-inflammatory pathway (CAP) concept, acetylcholine has been shown to be important for signal transmission within the immune system and also for a variety of other functions throughout the organism. The spleen is thought to play an important role in regulating the CAP. In contrast, the existence of a “non-neuronal cardiac cholinergic system” that influences cardiac innervation during inflammation has been hypothesized, with recent publications introducing the heart instead of the spleen as a possible interface between the immune and nervous systems. To prove this hypothesis, we investigated whether selectively disrupting vagal stimulation of the right ventricle plays an important role in rat CAP regulation during endotoxemia. We performed a selective resection of the right cardiac branch of the Nervus vagus (VGX) with a corresponding sham resection in vehicle-injected and endotoxemic rats. Rats were injected with lipopolysaccharide (LPS, 1 mg/kg body weight, intravenously) and observed for 4 h. Intraoperative blood gas analysis was performed, and hemodynamic parameters were assessed using a left ventricular pressure-volume catheter. Rat hearts and blood were collected, and the expression and concentration of proinflammatory cytokines using quantitative reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assay were measured, respectively. Four hours after injection, LPS induced a marked deterioration in rat blood gas parameters such as pH value, potassium, base excess, glucose, and lactate. The mean arterial blood pressure and the end-diastolic volume had decreased significantly. Further, significant increases in blood cholinesterases and in proinflammatory (IL-1β, IL-6, TNF-α) cytokine concentration and gene expression were obtained. Right cardiac vagus nerve resection (VGX) led to a marked decrease in heart acetylcholine concentration and an increase in cardiac acetylcholinesterase activity. Without LPS, VGX changed rat hemodynamic parameters, including heart frequency, cardiac output, and end-diastolic volume. In contrast, VGX during endotoxemia did not significantly change the concentration and expression of proinflammatory cytokines in the heart. In conclusion we demonstrate that right cardiac vagal innervation regulates cardiac acetylcholine content but neither improves nor worsens systemic inflammation.
Gesehen am 20.04.2018